Transport logistics as a component of logistics in tourism - Nefedova, N.; Nikolaieva, O.; Sokolovskiy, V.; Shashero, A. (Journal of Education, Health and Sport, 2025)
The article is devoted to the characteristics of transport logistics as a component of logistics in tourism. The historical stages of the formation of transport and logistics networks and systems as the basis for the development of tourism activities are presented. The dynamics of tourist flows by tourist regions from 1990 to 2024 are analyzed. The features of transport and logistics systems of different countries of the world, which have their own characteristics, are considered, taking into account such factors as geographical location, natural resource potential, relief, climate, landscape, etc. A description of popular tourist routes in the world is given.